SPECIES COMPOSITION, DISTRIBUTION AND RELATIONSHIP BETWEEN GOBY COMMUNITIES AND ENVIROMENTAL FACTORS AND HABITATS IN DOWNSTREAM AREA OF THU BON RIVER, QUANG NAM PROVINCE - Thao, Tran Thi Phuong; Long, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2018)
The study was conducted at three sites representing large variation in gradient of salinity from very low (Thanh Ha) to medium (Cam Nam) and high (Cam Thanh) in rainy (12/2015) and dry seasons (6/2016) in downstream area of Thu Bon river. At each site, goby species were sampled with traps and measurements of enviromental factors (pH, temperature, salinity, dissolved oxygen) and habitats (cover of freshwater weeds-grass, nypa palm-seagrass, sand-mud, mud-sand) were conducted at the 3 sites mentioned above. A total of 14 species belonging to 2 families Gobiidae (8 species) and Eleotridae (6 species) were recorded in rainy and dry seasons, in which the brackishwater site (Cam Thanh) supported the higher number of species (12 species) compared to the transitional site (Cam Nam: 6 species) and the freshwater site (Thanh Ha: 10 species). Results of annalyzing canonical correspondence between goby communities and the enviromental factors and habitats indicate that the distribution of goby community was mainly influenced by pH, salinity, dissolved oxygen and benthic cover of freshwater seaweeds-grass